Moderato: Master and disciple - A Case Study in the Olympic Landscape - Kosiewicz Jerzy (Sciendo, 2018)
The text characterizes the master-disciple relationship, which is interpreted in a historical context (of ancient Greece) and the contemporary one. In the first case it refers to the connection taking place between Socrates and his disciples (and especially between him and Plato). In the second case the author presents a study of one case of a supposed master-disciple relationship as a typical case study. He comes to a conclusion that the occurrence of such a relationship depends on two persons: a master and a disciple. When both of them agree that there was, there is and, maybe, there will be such a connection between them, it can be proclaimed with certainty that such a relationship existed or can start to exist. However, when any party of the supposed relationship is of an opinion that it has never existed, it is necessary to concede that (s)he is right, since it is not proper when one party maintains against the second party's will - or without his/her knowledge - that there was a master-disciple relationship between them.